Determination of heisenberg exchange coupling constants in clusters with magnetic sites: A local spin approach - Alcoba, Diego Ricardo (2014)
This work studies the ability of the two-center local spin quantities, provided by the partitioning of the expectation value of the spin-squared operator math formula corresponding to N-electron systems, for determining spin-exchange coupling constants within the Heisenberg spin Hamiltonian model. The spin-exchange parameters, which characterize this Hamiltonian for a determined system, have been evaluated in the HeH2 aggregate and in several math formula clusters (n = 2, 3, 4) with different geometrical arrangements, using internuclear distances larger than the equilibrium ones (beyond the bonding regions). The results found have been analyzed and compared with those arising from other approaches, showing the feasibility of our methodology.